Automated measurement of lamellar thickness in human bone using polarized light microscopy - Nicolas Ryan; Sandra J Shefelbine; Frederic Shapiro (MethodsX, 2023)
Lamellar bone formed in individuals with moderate and severe osteogenesis imperfecta (OI) is often composed of lamellae that are structurally abnormal. Measuring the thickness of these lamellae can be helpful in assessing the effect of specific collagen and collagen-related mutations on OI bone synthesis.Manual measurement of lamellar thicknesses in large quantities is very time consuming. The method for automated measurement described in this article utilizes an image processing script to identify the average thickness of multiple lamellae automatically from histologic images of bone. This allows for faster measurements that are less prone to human error and can account for variability in the thickness of a lamella along its length. • OI and control bone samples are prepared per the glycol methacrylate resin (JB-4 plastic) technique and viewed using polarized light microscopy. • Ideal bone regions for measurement are identified using specific qualitative criteria designed to ensure uniform and accurate thickness measurements. • The method was validated with dataset containing 211 lamellae from control bone and 212 lamellae from OI bone.